Визначення структури і генезису професійного образу студентів-психологів - Кордунова, Наталія Олександрівна; Kordunova, Nataliia O. (Інститут психології імені Г. С. Костюка НАПН України, 2014)
У статті проаналізовано теоретичні підходи й представлений опис емпіричного дослідження чинників, що визначають структуру і генезис професійного образу студентів-психологів.

The article analyzes the theoretical approaches and represented description of empirical research of factors, determining the structure and genesis of professional image of students-psychologists. In introduction of the article the actuality of the theme is grounded, various conceptual approaches to the study of the structure and genesis of professional image of students-psychologists are analyzed, and also the basic aspects of consideration of this problem in scientific literature are covered. Psychological researches indicate that determinations of the structure and genesis of professional image manifest and change during the study at higher educational establishment. The structure of professional image of students-psychologists is at least two-component and includes: the idea of the subject of professional activity and the idea of the activity content, object, aim and means in particular. The article underlines that basic factors of the structure of professional image are: ensuring their completeness, validity, timeliness and reliability. Indicators of occupational choice are two groups of motives: 1) desire to help people "to humanize" society and 2) desire to resolve own psychological problems, ensure personal growth and self-development. It is shown that professional competence of psychologists is at least two-tier and includes both relatively variable ("superficial") ideas and more stable representative "core" (substantive ideas – about the image of results of activity and means to achieve them). It is they to define the configuration of categorial assessment schemes of psychic reality, used by professionals. It is confirmed that structure and genesis of professional image of students-psychologists perform the important function of cognition instrument, i.e. description, classification and explanation of psychological phenomena. Close to the above-named is the second – adaptive function of ideas that turned out in coordination of unusual, unexpected phenomena by introducing them into the usual system of values. The third function – self-expression, which allows the specialist to feel like the owner of "mysterious knowledge", "engineer of human souls" that fosters Self-concept and protects the "I" from criticism and encroachments on the part of non-specialists. The fourth function – social identification, i.e. awareness of belonging to the professional workshop of psychologists, enabling professional communication, recognition of merits, etc. Found out that basic elements of professional and psychological world picture arise in the initial period of professional self-identity and do not undergo radical changes in the process of further professional socialization. Determined that the structure and genesis of professional image of students-psychologists is formed at the junction of scientific and theoretical and life and practical cognition of psychological nature of man and society, as a result differs in internal contradiction, electivity, use of conventional schemes of interpretation of psychological reality, stereotype.
Determinations of the structure and genesis of professional image of students-psychologists
Keywords: генезис; структура; компетентність; професійні уявлення; професія; психолог; genesis; competency; professional orientation; professional ideas; professional image; professional choice; profession; psychologist; student; student; structure